Characterization of a 520 kb deletion on chromosome 15q26.1 including ST8SIA2 in a patient with behavioral disturbance, autism spectrum disorder, and epilepsy. Issue 3 (19th December 2013) - Kamien, Benjamin; Harraway, James; Lundie, Ben; Smallhorne, Lex; Gibbs, Vicki; Heath, Anna; Fullerton, Janice M.
<x xml:space="preserve">Abstract</x> We present a patient with a behavioral disorder, epilepsy, and autism spectrum disorder who has a 520 kb chromosomal deletion at 15q26.1 encompassing three genes: ST8SIA2, C15orf32, and FAM174B. Alpha‐2, 8‐Sialyltransferase 2 (ST8SIA2) is expressed in the developing brain and appears to play an important role in neuronal migration, axon guidance and synaptic plasticity. It has recently been implicated in a genome wide association study as a potential factor underlying autism, and has also been implicated in the pathogenesis of bipolar disorder and schizophrenia. This case provides supportive evidence that ST8SIA2 haploinsufficiency may play a role in neurobehavioral phenotypes. © 2013 Wiley Periodicals, Inc.